PELAKSANAAN PEMBERIAN BANTUAN HUKUM TERHADAP TERDAKWA YANG TIDAK MAMPU DALAM PERKARA PIDANA DI KOTA BANDAR LAMPUNG - Andry Rahman Arif (Universitas Lampung, 2015)
Legal assistance is implemented through the courts, and legal aid legal aid program is provided in order to alleviate the burden of life for the people who cannot afford in terms of Economics, and is also useful to create justice and legal protection of the general public. Problems in this research is how the implementation of the granting of legal aid to defendants who cannot afford in terms of economy in criminal cases and the factors restricting implementation of granting legal aid to defendants who cannot afford in terms of economy in criminal cases. Based on the research results, and a discussion of the analysis of the implementation of legal aid to defendants who cannot afford in terms of economy in criminal cases, the implementation of the granting of legal aid can be done with the way through the courts, and the legal aid Institute (LBH) and can also be done by direct initiative of an advocate who voluntarily want to accompany her. Factors restricting implementation of granting legal aid to defendants who cannot afford in terms of economy in criminal cases among others; factors in law enforcement, community factors, cultural factors, facilities and infrastructure. Advice that can be given is the need for socializing by the court party, and about the implementation of the LBH granting legal assistance free of charge to the defendant who cannot afford, and to the need for sanctions to parties who caused the implementation of the grant of legal aid to the defendants engaged in criminal cases.Keywords: Granting Of Legal Aid, the Defendant, Not Being Able To, Criminal Cases